A NEW QoS GUARANTEE SLA BASED-SCHEME FOR HANDOFF CALLS IN WIRELESS NETWORKS - Nguyen Cao Phuong; Tran Hong Quan; Sang-Ho Lee; Jung-Mo Moon (ASEAN Journal on Science and Technology for Development, 2008)
The most important thing is guarantee QoS over wireless infrastructures. The efficient of service level agreement (SLA) is becoming increasingly important to both service providers and customers. This paper presents some traffic control schemes for improving QoS, trafficmodel and performance evaluation are described. We are defining a new scheme for improving handoff call performances in wireless networks, a finite queuing scheme for the handoff calls. SLA measurement calculates the packet delay parameter (PD) of handoff calls. The handoff calls will be accepted into queue if their PD will be smaller than the average waiting time of the queue. Important performance measures of the suggested scheme such as the blocking probability of new call and dropping probability of handoff call are described and evaluated.